Seafood processing activities among women in Ibeju-Lekki Local Government Area of Lagos State, Nigeria (2013)
The importance of seafood can never be over-emphasised because of its contributions to the various aspects of human life. However, the handling and processing of seafood are essential complimentary functions of all production system. This study was conducted to determine the seafood processing activities in Ibeju-Lekki Local Government Area of Lagos State, Nigeria. Purposive sampling technique was employed to select 101 women seafood processors while data collection was done using structured questionnaire and interview schedule. The data was analysed using only descriptive statistics. The results showed that most (34.7%) of the women processors were between ages 31 and 40 years, married (60.4), attained secondary level of education (64.4), practised Christianity (45.5) and Islam (44.6). Shrimps (45.0%), prawn and crabs were the type of seafood mostly processed by the respondents while smoking (31.4%) processing was the predominant processing method being used. The respondents acquired information on seafood processing through seafood processors association (91.1%). The major constraint facing respondents were health hazards (97%) and lack of capital (74.3%). Thus, women are actively involved in seafood processing in the study area and provision of basic infrastructure such as health care services would encourage the processors to increase their scale of operation.